EFFECTIVENESS APPROACH CONTEXTUAL TEACHING AND LEARNING (CTL) ON THE MATHEMATICS LEARNING OUTCOMES IN EVEN SEMESTER OF VII GRADE - Mita Maretta Ningtias; Widayati Widayati (Universitas Ahmad Dahlan, 2018)
The teachers still dominate learning mathematics, and some students still assume that mathematics is a hard subject. The lack of student activeness in learning mathematics in the class resulted in low student learning outcomes. Fortunately, there is one way to improve the students' learning outcomes by using the Contextual Teaching and Learning (CTL) approach. This study aims to determine the effectiveness of the learning approach Contextual Teaching and Learning (CTL) approach with conventional learning. The study is done in MTs Sultan Hadlirin Mantingan District Jepara. This study population was the seventh-grade students of Islamic Junior High School Sultan Hadlirin mantingan (MTs Sultan Hadlirin Mantingan) School Year 2016/2017, which comprises of 3 classes with a total of 68 students. The experiment class was VIIA, and class VII B as the control class that was selected by random sampling of classes. The methods of data collection using documentation and test. The research instrument is in the form of questions. The test instrument is used for validity, reliability, and distinguishing features. Prerequisite test data analysis is used for Normality Test, Homogeneity Test, and Hypothesis Testing. Hypothesis test results with a significance level of 5% and 46 degrees of freedom showed that: (1) there are differences in learning outcomes of mathematics that using approach Contextual Teaching and Learning (CTL) approach with conventional learning. It can be seen in = 8,0383 and = 2,0130, so > and (2) Learning mathematics using approach Contextual Teaching and Learning (CTL) approach is more effective than conventional learning. This is indicated by the value = 8,0383 and = 1,6787, so > .